Utilization of Generative Artificial Intelligence to Improve the Creative Writing Skills of High School Students - Rischi Utami, Ayu (EduTech Journal, 2025)
The use of generative AI such as ChatGPT, Copilot, and Gemini in creative writing learning has had a significant impact on improving students' writing skills. This research aims to explore the contribution of generative AI in enhancing students' creativity, imagination, and writing structure, as well as the ethical challenges associated with its use. The results show that generative AI speeds up the writing process, helps students overcome the impasse of ideas, and increases their confidence in writing. However, there are challenges related to plagiarism, reliance on technology, and decreased originality of students' writing. The wise use of AI requires effective teacher supervision, the development of AI literacy, as well as pedagogical adaptations to ensure that AI serves as a tool that enriches creativity without replacing students' personal voices. Therefore, the integration of generative AI in creative writing learning requires a careful approach, where technology is used to strengthen students' ability to think critically and create original works. This research provides important insights into the potential and challenges that need to be considered in the implementation of AI in writing education.